The Role Of Ecology In The Development Of Cardiovascular Diseases - Kasimova Kh.T. (Global Scientific Publishing, 2024)
Cardiovascular diseases (CVD) are among the most widespread health problems globally, being a leading cause of mortality. Ecological factors, such as air pollution, industrial waste, the ecological quality of food, and the density of urban areas and industrial centers, significantly influence their development. Research indicates that ecology directly or indirectly impacts the development of cardiovascular diseases. This paper presents conclusions drawn from modern scientific studies and statistical data to analyze ecological factors and understand their effects on CVDs. Additionally, recommendations are given on managing ecological factors and improving heart health
Keywords: Cardiovascular diseases; ecology; air pollution; cardiovascular diseases